ANALISA PERMINTAAN AIR MINUM ISI ULANG REVERSE OSMOSIS (RO) DI KOTA MEDAN - Ragyl Arieyanto; Wahyu Ario Pratomo (Departemen Ekonomi Pembangunan USU, 2014)
This study aims to determine the that influence consumer demand to buy refill drinking water RO types based on price , quality, place / location, and promosi.Untuk determine the most dominant factor affecting the consumer demand to buy RO water refill in the city of Belawan.The data war obtained from a sample of 50 customers buyers RO water refill. Tests using five indicators of factors of production, factor price, location , promotion sales and purchase interest. The research method used is descriptive analysis, statistical analysis and statistical analysis of F test The F in F table is 2.706> 2.61. At α = 5%Based on the results the, regression test results obtained by the value of the product is positive at 0.382, the value is positive rates of 0.206, where the value is positive at 0.356 and is positive promotional value of 0.056, which means that the most dominant factor in influencing consumer purchasing water content RO water is particularly re-factor of the product. So as to increase sales entrepreneurs drinking water should always keep that produced water production and also promotion again.Keywords: Factors of production, price, and production